2021
DOI: 10.3390/ijerph18115638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Timeliness of Male Shoulder Joint Endurance

Abstract: Acupuncture as a traditional and commonly used treatment has been used to improve the performance of athletes. In the improvement of female shoulder joint explosive force and muscle endurance also has an immediate effect. However, whether the effect of acupuncture therapy can be maintained after improving athletic performance still worth further discussion. The purpose of this study was to explore the timeless of the physical neurophysiological response induced by acupuncture at specific acupoints in improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This suggests that acupuncture can increase the explosive force of the male shoulder joint. A study from the same group done on 17 division III male athletes found that these same improvements can be sustained for up to 13 to 33 min posttreatment (52). Mead et al (53) performed dry needling on the legs of 10 active healthy college aged individuals, using the other leg as a control.…”
Section: Strength and Powermentioning
confidence: 93%
“…This suggests that acupuncture can increase the explosive force of the male shoulder joint. A study from the same group done on 17 division III male athletes found that these same improvements can be sustained for up to 13 to 33 min posttreatment (52). Mead et al (53) performed dry needling on the legs of 10 active healthy college aged individuals, using the other leg as a control.…”
Section: Strength and Powermentioning
confidence: 93%
“…The acupoints LI 15 (Jianyu), SJ 14 (JianLiao) were defined as points that are usually used to treat shoulder pain in a cross-sectional matched case-control study [ 33 ]. The acupoint LU3 (Tianfu) was used for its effect on muscle endurance in the female and male shoulder joints [ 34 , 35 ]. The acupoint GB35 (Yangjiao) was used in a study that investigated the effects of aconitine via acupoint injection in rabbits [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Consulting the most recent articles available on Pubmed/Medline (search performed in June 2021), the term explosive is associated with force (48), strength (38), power (29), performance (46), exercise (41), movements (5), contraction (28), and training (25). It is employed in the description of high-intensity brief tasks (e.g., jumps, kicks, sprints, strikes, throws, and weightlifting) (21,53), performance on neuromuscular evaluations (4,28,32), and in the description of strength and power training exercises as the plyometrics (36).…”
Section: Appropriate Terminologies Measurements and Unitsmentioning
confidence: 99%
“…Unfortunately, several studies have made the error of referring to these biomechanical concepts as 'explosive force' (11,37,40,48) or 'explosive strength' (4,9,12,15,30,38,42). The use of these superfluous terms may cause confusion and misunderstanding as readers may believe that these constructs represent different parameters beyond those which were measured.…”
Section: Explosive Force/strengthmentioning
confidence: 99%